Pelatihan manajemen keuangan sederhana bagi UKM di Kecamatan Benai, Kabupaten Kuantan Singingi - Ruzikna Ruzikna; Lie Othman; Lena Farida; Frini Karina Andini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
SME (Small Medium Entreprise) potentials to this extent, not enough to be able to maximum, otherwise many businesses SMES (owners) often have internal problems so it is difficult to develop and compete both between SMES and with the big producers. This relates to the problem of financial management which is one of the problems often encountered in SMES. Generally, the perpetrators of this activity start their efforts by having a reckless capital without being equipped with long-term capitalization plans as well as managerial skills and knowledge needed in entrepreneurship. This training aims to make the community or people of SMES in Kuantan Singingi District can optimize its business and can develop its business to improve the community economy. With this training the community becomes able to finance its business, as well as able to compete with larger producers later. This activity is conducted with a lecture model, discussion, and practice directly to prepare financial statements. This activity is also open to share problems faced by SMES in Kuansing District, so it will get solutions to the problems that occur. The results gained from this training are the increase in knowledge and ability of business actors to develop financial statements so that they can improve community SMES and lead to the improvement of the development and welfare of society.